2004
DOI: 10.1117/12.536681
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive aerostructures: the first decade of flight on uninhabited aerial vehicles

Abstract: Although many subscale aircraft regularly fly with adaptive materials in sensors and small components in secondary subsystems, only a handful have flown with adaptive aerostructures as flight critical, enabling components. This paper reviews several families of adaptive aerostructures which have enabled or significantly enhanced flightworthy uninhabited aerial vehicles (UAVs), including rotary and fixed wing aircraft, missiles and munitions. More than 40 adaptive aerostructures programs which have had a direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…This was followed by the first rotorcraft, Gamara, in December 1996, the first VTOL MicroAerial Vehicle (MAV) in September 1997 and a number of missile and munition flight control surfaces through the late 1990's. [2]- [8] These actuators generated significant deflections as seen in Figure 1. In addition to possessing high deflection capability, they also possessed high bandwidth and very low power consumption through the entire speed range.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…This was followed by the first rotorcraft, Gamara, in December 1996, the first VTOL MicroAerial Vehicle (MAV) in September 1997 and a number of missile and munition flight control surfaces through the late 1990's. [2]- [8] These actuators generated significant deflections as seen in Figure 1. In addition to possessing high deflection capability, they also possessed high bandwidth and very low power consumption through the entire speed range.…”
Section: Introductionmentioning
confidence: 96%
“…Because the flight control systems were both aerodynamically and inertially balanced, no flutter tendencies were ever observed in any wind tunnel or flight test. [8] However, their "soft spring" deflection properties at the limits of their stroke meant that buffet and stall loads simply could not be resisted. Figure 2 shows the typical actuator moment generation decay with increasing deflection which is a hallmark of early piezoceramic actuator elements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1996 a rotary wing UAV showed that flight control weight could be cut by 40% while decreasing both power consumption and drag simultaneously [8,9]. In 2000 it was shown that by using shape-memory-alloy filaments the pitch of the individual wings could be altered, thereby generating large control forces [10]. An important disadvantage however, was the increase in power consumption by a factor of two compared to conventional electromechanical actuators.…”
Section: Introductionmentioning
confidence: 99%
“…These overview papers described many approaches and listed several different techniques and approaches for achieving flight control. One of the later overview papers summarized not only rotorcraft, but missile, munition, and UAV successes which were numerous by 2004 [32].…”
Section: Solid State Adaptive Rotormentioning
confidence: 99%